Электропитание устройств связи: учебник для вузов - Бокуняев А. А. Александр Александрович; Горбачев Б. В. Борис Васильевич; Китаев В. Е. Валентин Евгеньевич; Колканов М. Ф. Михаил Федорович (Москва, Радио и связь, 1988)
Авт. указаны на обороте тит. л.